199 Effect of the Pelleting Process on Diet Formulations with Varying Levels of Crystalline Amino Acids and Reducing Sugars on Digestibility in Growing Pigs. (7th May 2021) - Dunmire, Kara M; Lopez, Diego A; Fiehler, Chance J; Zhang, Yiqin; Jones, Cassandra K; Li, Yonghui; Woodworth, Jason C; Goodband, Robert D; Tokach, Mike D; Stark, Charles R; Stein, Hans H; Paulk, Chad B
Abstract: The objective of this study was to determine effects of pelleting on the standardized ileal digestibility (SID) of amino acids (AA) in diets with or without increased concentrations of free AA and reducing sugars (RS). Eight individually housed, ileal cannulated barrows (initially 69.2 kg) were allotted to a replicated 8×8 Latin square with 8 diets and eight 7-d periods with ileal digesta collected on d 6 and 7. Treatments were arranged in a 2×2×2 factorial with main effects of diet form (mash vs. pellet), crystalline AA (low vs. high), or reducing sugars (low vs. high) provided by dried distillers grains with solubles and bakery meal. Diets were pelleted to achieve a hot pellet temperature of 85 to 88°C. Data were analyzed as a completely randomized Latin square using the GLIMMIX procedure of SAS. A feed form×RS interaction (P < 0.026) for SID of tryptophan was observed. Feeding pelleted low RS diets improved SID of tryptophan compared with mash high and low RS diets, and pelleted high RS diets. For main effects of feed form, the SID of total AA, CP, and indispensable AA increased (P < 0.042) in pigs fed pelleted diets compared with mash diets. For main effects of crystalline AA, pigs fed high crystalline AA had increased (P = 0.007) SID of tryptophan and decreased (P = 0.050) SID of histidine compared with those fed low crystalline AA diets. For main effects of RS diets, pigs fed high RS diets had decreased (P < 0.05) SID of total AA, CP and indispensable AA. In conclusion, pelleting diets with increased crystalline AA or RS did not affect the improvement in AA digestibility from pelleting. Pelleting diets improved AA digestibility. Diets formulated with high crystalline AA had increased SID of tryptophan. Formulating diets with high RS resulted in decreased AA digestibility compared with corn-soybean meal-based diets.